2021
DOI: 10.1158/2159-8290.cd-20-0872
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Therapeutic Targets for Fibrolamellar Carcinoma Using Patient-Derived Xenografts and Direct-from-Patient Screening

Abstract: fibrolamellar carcinoma drug repurposing pediatric rare tumors patient derived xenografts drug screening fusion gene Abbreviations: ATR -Ataxia telangiectasia and Rad3-related protein AURKA -Aurora kinase A AURKB -Aurora kinase B Bcl-xL -B-cell lymphoma-extra large encoded by the BCL2-like 1 gene Bcl2 -B-cell lymphoma 2 ITS -Insulin, (human) Transferrin, Selenium BID -BH3 Interacting Domain Death Agonist BIM -Bcl-2-like protein 11 CA12 -Carbonic anhydrase 12 CDc7 -Cell division cycle 7-related protein kinase C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 47 publications
5
46
0
Order By: Relevance
“…To contrast the transcriptomic profile in the organoids with the patient tissue, in Figure 4 D we compared the expression of these genes in the FLC-derived organoids (y axis) and the FLC tumors (x axis) relative to the adjacent non-transformed tissue. For the 509 genes of the consistent “fibrolamellar signature” that we have previously defined ( Lalazar et al., 2021 ), we obtained a Pearson correlation coefficient of 0.82 ( Figure 4 D).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…To contrast the transcriptomic profile in the organoids with the patient tissue, in Figure 4 D we compared the expression of these genes in the FLC-derived organoids (y axis) and the FLC tumors (x axis) relative to the adjacent non-transformed tissue. For the 509 genes of the consistent “fibrolamellar signature” that we have previously defined ( Lalazar et al., 2021 ), we obtained a Pearson correlation coefficient of 0.82 ( Figure 4 D).…”
Section: Resultssupporting
confidence: 52%
“…Sample 14 ∗ was isolated in an alternative medium for liver tumors, which replaced the Noggin, Rspo-1, and Wnt3a with 3 nM dexamethasone ( Broutier et al., 2017 ). (D) We have generated a “fibrolamellar signature” representing 509 transcripts ( Lalazar et al., 2021 ). The change in expression of these genes in the FLC-derived organoids relative to organoids derived from non-transformed liver tissue was plotted as a function of the expression in FLC tumor relative to the adjacent non-transformed tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The alternative conformation of the holoenzyme containing the DNAJB1-PRKACA fusion protein and the PKA regulatory subunit may constitute a strategy for selectively targeting the activity of the DNAJB1-PRKACA fusion protein (40). In addition, primary and metastatic FLC were shown to be sensitive to clinically available inhibitors of topoisomerase 1 and histone deacetylases, and to napabucasin (41), suggesting these agents as potential therapeutic strategies for FLC. The authors observed a variable response to PKA inhibitors, which may be due to the lack of sensitivity of the in vitro culture system (41).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We characterized and validated an FLC PDX mouse model ( 27 (40). In addition, primary and metastatic FLC were shown to be sensitive to clinically available inhibitors of topoisomerase 1 and histone deacetylases, and to napabucasin (41), suggesting these agents as potential therapeutic strategies for FLC. The authors observed a variable response to PKA inhibitors, which may be due to the lack of sensitivity of the in vitro culture system (41).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Another current trial (ClinicalTrials.gov identifier NCT04248569) examines the efficacy of a peptide vaccine against the DNAJB1‐PRKACA fusion combined with checkpoint inhibition in FLC; results from that trial are pending. A trial of checkpoint inhibition alone in pediatric HCC is enrolling (ClinicalTrials.gov identifier NCT04134559); we expect that these pending data, in conjunction with ongoing bench research, will better inform future treatment algorithms 20,36 . We hope that increased awareness of FLC and pediatric cHCC as distinct diseases will lead to additional efforts to develop novel therapies for these patients because repeat, aggressive resection (including metastatic disease in FLC) is currently their most effective option.…”
Section: Discussionmentioning
confidence: 99%